Peningkatan Aktivitas Kencan Online di Masa Pandemi - Balqis, Naura Adzillina; Noorrizki, Rakhmaditya Dewi (Flourishing Journal, 2022)
Abstract: One of the phenomena that occurred during the Covid – 19 pandemic was the increase in online dating activity. When compared to previous years, there is a very high increase in the use of online dating access, such as Tinder, Bumble, and Hinge applications. This also brings huge benefits to the holder of online dating access. The purpose of the researcher here is to find out what causes this phenomenon to occur with previous theories. The theory used is the theories proposed by Finkel, Toma, Hancock, and other genius inventors written in the book entitled Social Psychology by Elliot Aronson, Timothy D. Wilson, Robin M. Akert, Samuel R. Sommers and Social Psychology Book An Introduction by Dr. Fatah Hanurawan. Not only that, researchers also use the data that has been collected to find the cause of the phenomenon that occurs. Keywords: online dating; pandemic; factors causing an increase in online dating Abstrak: Salah satu fenomena yang terjadi saat pandemi Covid-19 terjadi adalah peningkatan aktivitas kencan online. Apabila dibandingkan dengan tahun- tahun sebelumnya, terdapat peningkatan yang sangat tinggi pada penggunaan akses kencan online, seperti aplikasi Tinder, Bumble, dan Engsel. Hal ini pun membawa keuntungan yang sangat besar kepada pemegang akses kencan online tersebut. Tujuan peneliti di sini ialah untuk mencari tahu apa saja penyebab fenomena ini terjadi dengan teori-teori terdahulu. Teori yang digunakan ialah teori-teori yang dicetuskan oleh Finkel, Toma, Hancock, dan penemu-penemu genius lainnya yang tertulis di dalam buku berjudul Social Psychology karya Elliot Aronson, Timothy D. Wilson, Robin M. Akert, Samuel R. Sommers serta buku Psikologi Sosial Suatu Pengantar oleh Dr. Fattah Hanurawan. Tidak hanya itu, peneliti juga menggunakan data-data yang telah terkumpulkan untuk mencari penyebab dari fenomena yang terjadi. Kata kunci: kencan online; pandemi; faktor penyebab peningkatan kencan online